Generation mean analysis and genetic parameters for yield and contributing traits in chickpea (Cicer arietinum) - KUMAR, RAVINDER; WALDIA, R S; KUMAR, RAMESH (The Indian Journal of Agricultural Sciences, 2012)
The genetics of yield and related traits in three chickpea crosses HC 5 × H 00 256, HC 5 × HC 3 and HC 1 × H 00 256 were studied using generation mean analysis. Over dominance was observed for pods and grain yield/plant (all crosses) and secondary branches/plant (HC 5 × HC 3 and HC 1 × H 00 256). Inbreeding depression was noticed in all the crosses for secondary branches/plant, number of pods/ plant and grain yield /plant. Both additive and dominance gene effects were significant for most of the traits, but the magnitude of later was high. The additive × additive interaction effects for most of the traits in all the crosses were also significant. Duplicate type of epistasis was noticed for 100- grain weight and plant height (all the crosses), grain yield/plant (HC 5 × H 00 256 and HC 1 × H 00 256) and primary branches/plant (HC 1 × H 00 256). The narrow sense heritability was low (